Nonlinear Effects in NOMA Systems Using Single Carrier Modulations: Performance Evaluation and Receiver Design - Oussama Ben Haj Belkacem; Rui Dinis; Mohamed Lassaad Ammari (IEEE Access, 2024)
Non orthogonal multiple access (NOMA) systems are very important for future communications which allows a huge increase in capacity gains when comparing to conventional orthogonal multiple access (OMA) techniques. On the other hand, the power consumption at the access point (AP) should be as low as possible, making single-carrier (SC) schemes, such as single carrier with frequency-domain equalization (SC-FDE), particularly interesting. In this paper, we consider power-efficient NOMA systems employing SC-FDE signals and present a generalized framework to characterize the signals at the output of a nonlinear device. We develop an accurate estimation of the power spectral density (PSD) of the signal associated to each user, showing that the nonlinear distortion effects on some users can be very high. Therefore, we introduce a joint iterative receiver for distortion compensation and interference cancellation based on SC-FDE characterized by low-complexity suitable for scenarios with strong nonlinear effects. Our performance results indicate that the proposed technique is able to reduce considerably the degradation associated to a high power amplifier (HPA) modeled as a memoryless polynomial and allow complexity improvements when compared to conventional schemes, especially when operating at low input back-off (IBO).